Motivasi Personal sebagai Penggerak Sumber Daya Pendidik di Era Digital Milenial - Wulandari, Baiduri; Supendi, Pepen (BISMA : Business and Management Journal, 2024)
This research analyzes motivation with several theories proposed by scientists and the motivation present in Islam to support the productivity of educational resources in carrying out their noble duties as teachers. One of the theories discussed here is Abraham Maslow’s motivation theory and how Islam perfects the concept of motivation itself. This research aims to find the best solution for educators regarding motivation as a driving force, which is sometimes felt less detectable or less sensitive to the decline in their motivation, thus requiring a separate space to find the solution. This research also aims to detect issues related to the causes of the decline in motivation, linked to the theory proposed by Abraham Maslow and refined by Islamic-oriented motivation, so that human resources in education can become stable or more enthusiastic in their roles as educators in the millennial digital era. This research method uses a qualitative approach through a literature review. The research successfully obtained findings in line with its objectives: the analysis of elements that can dampen motivation or even reduce or eliminate the motivation of educational resources in the millennial digital era. The five basic human needs expressed by Abraham Maslow are the elements that influence the motivation of human educational resources. The theories presented are human experiences encountered by humans as educational resources, complemented by Islamic knowledge related to motivation as a driving force for educational resources in the millennial digital era.